APPLICATIONS OF PHYSICAL THERAPY IN THE REHABILITATION OF PATIENT WITH CEREBRAL TUMORS: FOURTH VENTRICLE INFILTRATION IN MEDULLOBLASTOMA - Cazac Gabriela Iuliana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Primitive brain tumors of the central nervous system are a major health problem. Most intraterritorial tumors affect functionally important areas of the brain and postoperative motor disability are unfavorable. Given its location, the fourth ventricle interposes between the cerebellum and the brainstem, therefore, a tumor that grows into the fourth ventricle, can produces a mechanical pressure on the nearby anatomical elements with specific symptoms. On a 15-year-old patient, diagnosed with medulloblastoma into fourth ventricle ( W.H.O. grade IV) molecular subgroups WnT, the initial tratament involved surgery to remove as much of the tumor as possible ( after two surgeries, some residual tumor was still left behind because it was too close to normal brain structures), then further treatment with chemotherapy and radiation therapy followed. After the treatment, the symptoms related (effects owing to the tumor itself and the effects of treatment) was: poor static and dynamic balance, truncal ataxia with impaired tandem gait, lack of the coordination and balance to walk safely and independently, (resulted from affecting the archicerebellum and paleocerebellum), appendicular ataxia (manifesting a difficulty with rapid alternating movements, fingernose-finger), hypotonia, poor coordination (asynergy, dysmetria- resulted from the affected neocerebellum), dysarthria, nystagmus (due to pressure on the brainstem- vestibular syndrome). The purpose of this study was to restore lost motor skills, prevent complications, maximize function, and improve the quality of life